Estudo de comunidades vegetais campestres na região do Alto Camaquã, Rio Grande do Sul - Boavista, Lidiane da Rosa (2012)
Understanding the dynamics of vegetation could facilitate decision making and adoption of new management practices, seeking a better use of available resources in areas of natural grassland. This study aimed to evaluate the dynamics of a natural grassland vegetation subject to grazing and fertilization, in four different locations in the counties of Pinheiro Machado and Piratini, located in the upper basin region of Rio Camaquã. The treatments were a combination of the above factors. The estimation of species composition and biomass followed BOTANAL field method procedures, with some adjustments. There was a change in vegetation dynamics in the treatments as a response of the interaction of evaluation period, fertilization and grazing, showing a divergence of the trajectories of vegetation and there is no clear distinction of functional types. There was not a clear association between the functional types and environmental variables. The diversity and evenness of species were quantified using the Shannon and equitability indexes. There were no significant differences between different fertilization, but for grazing, there was a significant difference between the evaluation periods. Areas subjected to controlled grazing, show a tendency to increase the diversity of species compared to areas subjected to continuous grazing. The use of controlled grazing had a positive influence on species diversity.